Acesso vascular definitivo em usuários de hemodiálise: construção e validação de uma escala de conhecimento - Pinto, Elda Garbo [UNESP] (2014)
Methodological nature study of the construction and validation of assessment tools in health, in order to build and validate knowledge scales about the permanent vascular access in hemodialysis users for nephrology nurses. The steps to prepare the scales were: practices selection involving permanent vascular access to hemodialysis users, theoretical basis of selected practices and development of guided scales in clinical guidelines (guidelines) Clinical practice guidelines for vascular Access, “Guías de Acceso Vascular em Hemodiálisis” (Espanish Society of Nephrology) and “Guía de acceso vascular en hemodialysis”. Thus, four scales were built : knowledge Scale of permanent vascular access in hemodialysis users (KSPVA) – Universal Care, knowledge Scale of permanent vascular access in hemodialysis users (KSPVA) – Specific Care, knowledge Scale of permanent vascular access in hemodialysis users (KSPVA) – physical examination and knowledge Scale of permanent vascular access in hemodialysis users (KSPVA) – Hemodynamic Monitoring. Data collection occurred from February to August 2013, using a questionnaire, consisting of the following parts : trial content (constructo), of the attributes and components of each built scale. The scales content validity was performed by twelve judges with extensive experience in the field of nephrology. All built scales were validated by professionals under minimum favorable consensus of 75 %. It is noteworthy that after validation, scales were applied to 84 nurses, working on renal replacement therapy in 3 centers in towns of São Paulo State, where 2.3% of the professionals have demonstrated little knowledge, 33.3 % have demonstrated satisfactory knowledge and 64.2 % of the professionals have demonstrated full knowledge about care and complications with AVF